Revisión de literatura: nuevas herramientas tecnológicas aplicadas al proceso de enseñanza-aprendizaje en el sector turístico - Díaz Sánchez, Alejandra Stefanía (2015)
This literature review makes an analysis of the new technological tools applied to the process of education - learning in the tourism sector. The principal intention is to announce the reader different points of view in relation to the impact of the ICT applied in this sector. The research was carried out in three chapters: literature review, methodology of investigation and analysis and presentation of results obtained. First, an introduction of the issue was defined based on a current context. Then, the literature review was developed using sources of high academic value to support the research. In chapter two research’s methodology was defined and which were the methods to retrieve appropriate information. Chapter three presents the analysis of the results obtained. Finally, the conclusions of this literature review are proposed.